KEFEKTIFITASAN MODEL PEMBELAJARAN TWO STAY TWO STRAY TERHADAP KEMAMPUAN BERBICARA SISWA KELAS IV SD NEGERI MANGUNHARJO SEMARANG - Bayu Saputro; Mei Fita Asri Untari; Mudzanatun Mudzanatun (Universitas Ngudi Waluyo, 2020)
The background of this research is the still centered learning of the teacher and the lack of courage of students to express an opinion, this is also supported by the incompleteness of Indonesian language learning, precisely in the speaking ability of fourth grade students of SD Negeri Mangunharjo Semarang. This study aims to determine whether the two stay two stray learning model is effective on the speaking ability of fourth grade students of SD Negeri Mangunharjo Semarang. This type of research is quantitative research using Pretest-Posttest one-Group Design. After taking the data, then analyzing the data of the pretest and posttest learning outcomes with the t-test that was obtained with an average pretest value of 57.12 and an average posttest value of 80.19. With N = 26, obtained tcount = 17.29282 with a 5% significance level of 2.055529. Because tcount = 17.29282> table = 2.055529. Then this shows that the t test has a significant effect. This shows that there is an effect of learning the Two Stay Two Stray (TSTS) model. Suggestions that can be delivered by researchers to teachers is that learning is not only centered on the teacher, but also involves the activeness of students in order to achieve enjoyable learning and students have an interest in learning.